Understanding Sustainability-oriented Innovation (SOI) Using Network Perspective in Asia Pacific and ASEAN: A Systematic Review - Budi Harsanto; Chrisna Permana (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2019)
Sustainability-oriented innovation (SOI) is particular type of innovation that is not only economically oriented, but also environmental- and social benefits-oriented. SOI is now being widely discussed due to the increasing environmental and social problems that accompany various innovations around the world. In this paper we conducted a systematic review of empirical literature regarding SOI in the Asia Pacific region, which were discussed through network perspectives. For network perspectives, researchers focused on process view to explain how SOI is mobilised and practised throughout different social, institutional, and political contexts. We chose the Asia Pacific as the context because the region is the most dynamic part of the global economy, with ASEAN being the prominent parts of it. In conducting the review, we used the Tranfield, Denyer, & Smart's protocol (2003) to ensure its rigorousness. The search focused on the academic database of Scopus with specific inclusion and exclusion criteria. The results show that SOI has been rapidly developing into practices in countries in the Asia Pacific, not only in profit sectors, but also in non-profit sectors such as government and community. Our review emphasised that actor-network theory (ANT) emerged as the currently most adopted framework to explain the dynamics process of SOI mobilisations and practices in the Asia Pacific region. ANT frameworks contribute to defining the structure of SOI networks as well as identifying social, institutional, and political challenges of SOI implementation. Regionally, the focus of the study so far is in North America (US and Canada), while studies in ASEAN are still very limited.